Importanța teambuilding-ului pentru echipele de bibliotecari. Experiența Bibliotecii Municipale „B.P. Hasdeu” în cadrul Colocviilor profesionale de vară - HARJEVSCHI, Mariana (BIBLIOPOLIS, 2026)
Libraries are constantly adapting to meet the diverse needs of the community, and teams of librarians need effective communication, solid cooperation and creativity to provide quality services. Teambuilding thus becomes an essential tool for strengthening professional relationships, stimulating innovation and developing collaboration skills. The article presents the experience gained within the “Think Outside the Box” activity, part of the 13th edition of the Professional Summer Colloquiums organized by the B.P. Hasdeu Municipal Library in partnership with ACTIVIS